(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In the current period, when our country has entered a new stage of its development path, issues of progressive discovery of the cultural sphere and further increase the effectiveness of the information factor in this area are becoming more important. Comprehensive reforms are also being carried out in this area; updates are taking place.